Differential procoagulant effects of saw-scaled viper (Serpentes: Viperidae: Echis) snake venoms on human plasma and the narrow taxonomic ranges of antivenom efficacies. (5th October 2017) - Rogalski, Aymeric; Soerensen, Christoffer; op den Brouw, Bianca; Lister, Callum; Dashevsky, Daniel; Arbuckle, Kevin; Gloria, Alexandra; Zdenek, Christina N.; Casewell, Nicholas R.; Gutiérrez, José María; Wüster, Wolfgang; Ali, Syed A.; et al.
Highlights: Saw-scaled vipers were shown to have a significant range in clotting times and cofactor dependence. Phospholipid dependence was shown to be inversely correlated with clotting time. Antivenom efficacy was strongly associated with taxonomy. Indian antivenoms were not able to neutralise African species. Abstract: Saw-scaled vipers (genus Echis ) are one of the leading causes of snakebite morbidity and mortality in parts of Sub-Saharan Africa, the Middle East, and vast regions of Asia, constituting a public health burden exceeding that of almost any other snake genus globally. Venom-induced consumption coagulopathy, owing to the action of potent procoagulant toxins, is one of the most relevant clinical manifestations of envenomings by Echis spp. Clinical experience and prior studies examining a limited range of venoms and restricted antivenoms have demonstrated for some antivenoms an extreme lack of antivenom cross-reactivity between different species of this genus, sometimes resulting in catastrophic treatment failure. This study undertook the most comprehensive testing of Echis venom effects upon the coagulation of human plasma, and also the broadest examination of antivenom potency and cross-reactivity, to-date. 10 Echis species/populations and four antivenoms (two African, two Asian) were studied. The results indicate that the venoms are, in general, potently procoagulant but that the relative dependence on calcium or phospholipid cofactors is highly variable. Additionally, three out of the four antivenoms tested demonstrated only a very narrow taxonomic range of effectiveness in preventing coagulopathy, with only the SAIMR antivenom displaying significant levels of cross-reactivity. These results were in conflict with previous studies using prolonged preincubation of antivenom with venom to suggest effective cross-reactivity levels for the ICP Echi-Tab antivenom. These findings both inform upon potential clinical effects of envenomation in humans and highlight the extreme limitations of available treatment. It is hoped that this will spur efforts into the development of antivenoms with more comprehensive coverage for bites not only from wild snakes but also from specimens widely kept in zoological collections.